Enhanced sulfide removal and bioelectricity generation in microbial fuel cells with anodes modified by vertically oriented nanosheets. Issue 14 (20th June 2019) - Yang, Meng; Zhong, Yuezhi; Zhang, Baogang; Shi, Jiaxin; Huang, Xueyang; Xing, Yi; Su, Lin; Liu, Huipeng; Borthwick, Alistair G.L.
ABSTRACT: Anode materials and structures are of critical importance for microbial fuel cells (MFCs) recovering energy from toxic substrates. Carbon-fiber-felt anodes modified by layers of vertically oriented TiO2 and Fe2 O3 nanosheets were applied in the present study. Enhanced sulfide removal efficiencies (both over 90%) were obtained after a 48-h operation, with maximum power densities improved by 1.53 and 1.36 folds compared with MFCs with raw carbon-fiber-felt anode. The modified anodes provided more active sites for microbial adhesion with increasing biomass densities. High-throughput 16S rRNA gene sequencing analysis also indicated the increase in microbial diversities. Bacteroidetes responsible for bioelectricity generation with Thiobacillus and Spirochaeta dominating sulfide removal were found in the MFCs with the modified anodes, with less anaerobic fermentative bacteria as Firmicutes appeared. This indicates that the proposed materials are competitive for applications of MFCs generating bioelectricity from toxic sulfide.